2021
DOI: 10.1186/s12891-021-04223-7
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of predatory journals and open access publishing among orthopaedic and trauma surgeons – results from an online survey in Germany

Abstract: Background Along with emerging open access journals (OAJ) predatory journals increasingly appear. As they harm accurate and good scientific research, we aimed to examine the awareness of predatory journals and open access publishing among orthopaedic and trauma surgeons. Methods In an online survey between August and December 2019 the knowledge on predatory journals and OAJ was tested with a hyperlink made available to the participants via the Germ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Various factors can account for deciding where researchers choose to publish findings (Niles et al, 2020), including pressure by institutions (Alamri et al, 2020; Cobey et al, 2019; Kurt, 2018), social identity threat, unawareness, lack of proficiency (Kurt, 2018), promises of a fast publication (Salehi et al, 2020), and impact factors and indexing in databases (Nicholas et al, 2017). These factors, combined with naivety from ECRs, authors, and even editors on the concept of predatory publishers (Alamri et al, 2020; Christopher & Young, 2015; Cohen et al, 2019; Maurer et al, 2021) and an array of tactics and features employed by predatory publishers (Memon, 2018) can result in continued submission to such predatory publishers.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors can account for deciding where researchers choose to publish findings (Niles et al, 2020), including pressure by institutions (Alamri et al, 2020; Cobey et al, 2019; Kurt, 2018), social identity threat, unawareness, lack of proficiency (Kurt, 2018), promises of a fast publication (Salehi et al, 2020), and impact factors and indexing in databases (Nicholas et al, 2017). These factors, combined with naivety from ECRs, authors, and even editors on the concept of predatory publishers (Alamri et al, 2020; Christopher & Young, 2015; Cohen et al, 2019; Maurer et al, 2021) and an array of tactics and features employed by predatory publishers (Memon, 2018) can result in continued submission to such predatory publishers.…”
Section: Discussionmentioning
confidence: 99%
“…DOAJ (https://doaj.org/) has existed since 2003 and is an independent database of 16,000+ open access journals. The journals are assessed according to a set of criteria (Olijhoek et al, 2015) and is being used to identify non‐predatory journals (Gallo et al, 2022; Maurer et al, 2021). Numerous examples of safe lists are available (Koerber et al, 2020, p. 3).…”
Section: Identifying Predatory Journalsmentioning
confidence: 99%
“…The prolific literature regarding terminology and definitions (Mertkan, Onurkan Aliusta, & Suphi, 2021) is not ideal which is also why a definition of these predatory behaviours is called for (Aromataris & Stern, 2020; Callaghan & Nicholson, 2020). Grudniewicz et al (2019, p. 211) present a consensus definition:
Predatory journals and publishers are entities that prioritize self‐interest at the expense of scholarship and are characterized by false or misleading information, deviation from best editorial and publication practices, a lack of transparency, and/or the use of aggressive and indiscriminate solicitation practices.
A number of recent studies show that knowledge as well as awareness of predatory journals tends to be low across disciplines and academic positions (AlRyalat et al, 2019; Atiso et al, 2019; Cohen et al, 2019; Kinde, 2021; Maurer et al, 2021; Richtig et al, 2019; Wang et al, 2021). On the other hand, other studies find that faculty are aware and recognize predatory journals as a problem (Owolabi et al, 2020; Swanberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A recent survey showed that only 40% of orthopaedic and trauma surgeons were aware of predatory journals, with the younger surgeons less familiar than their older cohorts. 2 Solicitation for these journals typically occurs in e-mail communications, and the targets are usually identified as authors who have published other works in conventional publications. These predatory journals process manuscripts without peer review and plagiarism checks, often for a nonsubstantial publication fee.…”
mentioning
confidence: 99%